Utilizing an E-Grammar Book to EFL learners: Analysing the Practicality Level - Nurul Fitriyah Almunawaroh; Kuntum Trilestari (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: English grammar competency will determine one’s competencies in listening, speaking, reading, and writing. While English grammar plays crucial roles in learning English language, it is the core of EFL students’ diffilties in learning English. Utilizing an e-book to teach English grammar to students will benefi them since it is provided with interactive features that can promote students’ motivation and understanding of English grammar. This study aims to fid students’ perspective on the use of an e-book with past tense materials towards its practicality and interactivity in motivating EFL student’s learning. The e-book was developed by using ADDIE model and the practicality level was gauged by administering close-ended questionnaire to EFL students. The results revealed that the e-book was practical with a very high practicality level which indicated that the e-book can be utilized by the students, and the students were motivated in learning English Grammar by using the e-book.Keywords: e-book, past tenses materials, practicality.Abstrak: Kompetensi tata Bahasa Inggris akan menentukan kompetensi seseorang dalam menyimak, berbicara, membaca, dan menulis. Meskipun memainkan peran penting dalam belajar bahasa Inggris, tata Bahasa Inggris adalah inti dari kesulitan yang dihadapi siswa dalam belajar bahasa Inggris. Memanfaatkan buku elektronik untuk mengajarkan tata bahasa Inggris kepada siswa akan menguntungkan mereka karena dilengkapi dengan fiur interaktif yang dapat meningkatkan motivasi dan pemahaman siswa tentang tata Bahasa Inggris. Penelitian ini bertujuan untuk mengetahui perspektif siswa tentang penggunaan e-book dengan materi past tense terhadap kepraktisan dan interaktivitas dari buku elektronik tersebut dalam memotivasi siswa belajar tata Bahasa Inggris. Buku elektronik dikembangkan dengan menggunakan model ADDIE dan tingkat kepraktisan diukur dengan memberikan kuesioner kepada siswa. Hasil penelitian menunjukkan bahwa buku elektronik praktis dengan tingkat kepraktisan yang sangat tinggi yang mengindikasikan bahwa buke elektronik dengan materi past tenses dapat digunakan siswa dalam mempelajari tata Bahasa Inggris, siswa pun termotivasi dalam mempelajari tata Bahasa Inggris menggunakan buku elektronik tersebut.Kata kunci: buku elektronik, materi past tenses, kepraktisan